Methodological analysis of capitalism and the concept of Max Weber social impact - Cheblakova, Liudmila A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article is devoted to methodological analysis of capitalism, it is «spirit» where as an instrument of social cognition according to Weber the category of an ideal types is considered. Social dialectics is stipulated by the social action of persons, which activity is motivated by specific religiously consciousness – the evangelical economical activity. Weber outlines the main axioms of the evangelical economical activity: diligence, integrity, economy, thoughtfulness.
Keywords: capitalism spirit; ideal type; retional society; social action; evangelical ethics